The Dynamics of Income-Related Health Inequalities in Australia versus Great Britain - Paul Samuel Calara; Ulf-G. Gerdtham; Dennis Petrie (Lund University, School of Economics and Management, Department of Economics, 2016)
This study compares the evolution of income-related health inequality (IRHI) in Australia (2001–2006) and in Great Britain (1999–2004) by exploring patterns of morbidity- and mortality-related health changes across income groups. Using Australian longitudinal data, the change in health inequality is decomposed into those changes related to health changes (income-related health mobility) and income changes (health-related income mobility), and compared with recent results from Great Britain. Absolute IRHI increased for both sexes, indicating greater absolute health inequality in Australia over this period, similar to that seen in Great Britain. The income-related health mobility indicates that this was due to health losses over this period being concentrated in those initially poor who were significantly more likely to die. The health-related income mobility further indicates that those who moved up the income distribution during the period were more likely to be those who were healthy. Australian estimates of mobility measures are similar, if not greater, in magnitude than for Great Britain. While reducing health inequality remains high on the political agenda in Great Britain, it has received less attention in Australia even though the evidence provided here suggests it should receive more attention.
Keywords: D39; D63; I18; 330; HILDA; BHPS; income-related health inequality; longitudinal analysis; vertical equity